The Values of Akidah Akhlak Education in the Harmonization of Sunan Kalijaga's Cultural Da'wah (Axiological Analysis of Islam and Javanese Culture) - Hafizh, Muhammad; Rifqi Zam Zami, Muhammad; Ferdian, Ferdian; Hamzah, Ghufron (Lembaga Penelitian dan Pengabdian Masyarakat Institut Agama Islam Al-Khairat Pamekasan, 2024)
The problem of this research is the da'wah of Sunan Kalijaga, which was based on local culture in the midst of Javanese society, which still embraced Hinduism and Buddhism at that time. The spread of Islam in Java faced theological, religious, and moral challenges because it was a new teaching. The research method used is a qualitative-library study using literature in the form of books and scientific research. The data was analyzed through descriptive analysis focusing on Sunan Kalijaga's cultural da'wah axiology. The results showed that Sunan Kalijaga's cultural da'wah involved the acculturation of Javanese culture and Islamic values, with the principles of upholding the cultural values of the Palace, enriching Islamic literature, considering social, cultural, and political stability, and being protected by the government. This da'wah's creedal and moral values include religious moderation, increasing religious harmony, and faith in Allah, the Prophet, and the Qur'an.